Geçmiş ve Günümüz Kodlarıyla Buryat Geleneksel Güreşi: Buhe-Barildaan - Türkmen, Mehmet; Okudan, Bilal (My University, 2020)
Tüm Türk halklarının Orta Asya'dan önceki kadim vatanı olan ve Güney Sibirya’da yaşayan Buryatlar,Türklerin kültürel ve genetik kodlarında ilk etkileşim yaptığı halklardan biridir. Buryatlar, ‘Buhe-Barildaan'denilen geleneksel güreşi eskiden beri popüler olarak yapmaktalar. Dışarıdan birisi için, Buryat gelenekselgüreşini anlamak, şüphesiz Buryat’ın ve hatta Türk halklarının sosyal hayatının diğer yönlerine de çok fazlaışık tutar. Onun için bu çalışma, ‘Buhe-Barildaan'ı oluşum, dönüşüm ve ritüelleri ile anlatmak amaçlanmıştır.Literatür taraması yapılmakla birlikte niteliksel yaklaşım içinde yer alan modellerden betimsel araştırma vekarşılaştırma yöntemi kullanılmıştır. Araştırma, Güney Sibirya coğrafyasında yaşayan Türk-Moğolhalklarından Buryatların folklorik güreşi ile sınırlandırılmıştır. Buryatların 'Buhe-Barildaan' güreşleri,‘orman’ ve ‘bozkır’ olarak iki tür ayırt etmişlerdir. Birincisi Oyratlar, Türk kökenli Bulaga ve EhiriBuryatları ile Onon Moğolları arasında ‘orman türü’ yaygınlık kazanmıştır. Şimdi hemen hemen her yerdeuygulanan ‘bozkır türü’ ise sadece hayvancılıkla uğraşan halklarda görülürdü. ‘Bozkır türü’ ne girenmüsabakalarda üç alandan birinin yere değmesi mağlubiyet getirirdi. Güreşe başlamadan önce üst giyimtamamen çıkarılır ve pehlivanların üzerinde ancak pantalonları kalır, çünkü böyle kapışmak daha rahattır.Güreşçiler birbirinin karşısına geçer ve güneşin yönüne göre dönerler. Sonuç olarak, rus olmayan yerliyazarlar, Buryat güreşinin önemini açıklamak, sosyal işaretler arasında bir devamlılık önermek, sosyal anlamve ulusal kimlik oluşturmak için çeşitli önerme efsanesini kullandıkları görüldü. Buryat güreş kültürü, halkıngelişimi ve sürekliliği için kendisine özgü olan iktisadi yaşamı ve bu yaşamı besleyen coğrafi ortamıngeleneksel kaynaklarına dayanıyor. Buhe-Barildaan güreşlerinin nesiller arasında milli kimliğin vebağlantının korunmasına yardımcı olan spor kültürünün en önemli unsurlarından biridir. Buryatların Buhebarildaan güreşlerinin işlevsel ve ideolojik kökenleri, tarihsel olarak, her şeyden önce, dış güçle yüzleşmekzorunda kalmanın yanı sıra askeri güçlerin lideri olan bir kitlenin seçimi ile ilişkilendirilir. Ayrıca, bozkır ve orman tipi olmak üzere iki türü görülen Buhe-barildaan güreşleri, tipolojik ve homojenlik bağlamında baştaTürkleri olmak üzere o coğrafyalarda yaşayan halkların güreşleriyle örtüştüğü görüldü.

Buryati, the ancient homeland of all Turkic peoples before Central Asia and living in Southern Siberia, are one of the first peoples that Turks interact in cultural and genetic codes. Buryats have been popular wrestling traditional wrestling called "Buhe-Barildaan" from ancient times. For an outsider, understanding Buryat traditional wrestling undoubtedly sheds a lot of light on other aspects of Buryat's and even Turkish peoples' social life. Therefore, this study is aimed to explain ‘Buhe-Barildaan with its formation, transformation and rituals.Along with the literature review, descriptive research and comparison method, among the models included in the qualitative approach, was used. The research is limited to the folkloric wrestling of Buryats, who are Turkish-Mongolian people’s living in Southern Siberia. Buryat 'BuheBarildaan' wrestling distinguished two types as 'forest' and 'steppe'. First of all, "forest type" has become widespread among the Oyrat, the Bulaga and Ehiri Buryats of Turkish origin, and the Onon Mongols. The 'steppe type', which is now practiced almost everywhere, was only seen in peoples dealing with animal husbandry. In the competitions of the "Steppe type", one of the three areas touching the ground would bring defeat.Before starting the wrestling, the top is completely removed and only the trousers remain on the wrestlers, because it is more comfortable to fight like this. Wrestlers face each other and rotate according to the direction of the sun. In conclusion, non-Russian native authors, to explain the importance of Buryat wrestling, to suggest continuity between social signs, they have been seen using various propositional myths to construct social meaning and national identity. Buryat wrestling culture, it is based on the economic life unique to the development and continuity of the people and the traditional sources of the geographical environment that feed this life. Buhe-barildaan wrestling is one of the most important elements of the sports culture that helps to preserve the national identity and connection between generations. The functional and ideological origins of the Buryat Buhe-barildaan wrestling, historically, it is associated, first of all, with the choice of a mass who, besides having to face external power, is the leader of the military forces. In addition, Buhe-barildaan wrestling, which has two types, namely steppe and forest types, was seen to coincide with the wrestling of the peoples living in those geographies, especially Turks, in the context of typology and homogeneity.
Buryat Traditional Wrestling with Past and Present Codes: Buhe-Barildaan